Evaluasi Pembelajaran Digital Bahasa Indonesia melalui Integrasi Google Form dan Buku Teks pada Siswa Kelas IX SMP/MTs - Sahril Hamdani; Liana Rochmatul Wachidah; Albaburrahim Albaburrahim; Mochamad Arifin Alatas (Social, Humanities, and Educational Studies (SHES): Conference Series, 2025)
This research is motivated by the development of technology that encourages teachers to combine textbooks with digital instruments such as Google Form to support the effectiveness of the learning evaluation process. This study aims to describe the use of Google Form and textbooks as evaluation tools for Indonesian language learning for grade IX students of junior high schools/Islamic junior high schools. The method used is a literature study with a qualitative approach, the data of which is obtained from reference books and scientific journal articles. Data analysis was carried out through the stages of data collection, data reduction, data presentation, and inference drawing. The results of the study show that the use of Google Form provides convenience in managing and accessing evaluation results quickly, while textbooks still provide varying depth of material and validity of questions. The collaboration between these two instruments has been shown to increase the efficiency and quality of Indonesian language learning evaluation. The conclusion of this study is that the integration of Google Form and textbooks is an effective and relevant digital evaluation innovation to support continuous learning in the technological era.Penelitian ini dilatarbelakangi oleh adanya perkembangan teknologi yang mendorong guru untuk mengombinasikan buku teks dengan instrumen digital seperti Google Form guna mendukung efektivitas proses evaluasi pembelajaran. Penelitian ini bertujuan untuk mendeskripsikan penggunaan Google Form dan buku teks sebagai alat evaluasi pembelajaran Bahasa Indonesia pada siswa kelas IX SMP/MTs. Metode yang digunakan adalah studi pustaka dengan pendekatan kualitatif, yang datanya diperoleh dari buku-buku referensi dan artikel jurnal ilmiah. Analisis data dilakukan melalui tahap pengumpulan data, reduksi data, penyajian data, dan penarikan inferensi. Hasil penelitian menunjukkan bahwa penggunaan Google Form memberikan kemudahan dalam mengelola dan mengakses hasil evaluasi secara cepat, sementara buku teks tetap memberikan kedalaman materi dan validitas soal yang bervariasi. Kolaborasi antara kedua instrumen ini terbukti meningkatkan efisiensi dan kualitas evaluasi pembelajaran Bahasa Indonesia. Simpulan dari penelitian ini adalah bahwa integrasi Google Form dan buku teks merupakan inovasi evaluasi digital yang efektif dan relevan untuk mendukung pembelajaran berkelanjutan di era teknologi.